Validitas dan Praktikalitas Modul Larutan Penyangga Berbasis Pendekatan Saintifik dengan Menerapkan Teknik Probing dan Promting untuk Kelas XI SMA/ MA - Wardhatul Jannah, Ellizar (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Curriculum 2013 recommends scientific approach in learning and expects studentsto be critical thinking. The research aim to develop a buffer module based on scientificapproach for XI SMA/ MA class and to determine validity and practicality level. Thisdeveloped module uses probing questions (digging questions) and promting (guidingquestions) to train critical thinking students. This research is Research and Development(R&D) with 4-D model. Validity test was done by 2 chemistry lecturers at FMIPA UNP, 1chemistry teacher at SMAN 7 Padang, 1 chemistry teachers at SMAN 12 Padang and 1chemistry teacher at SMAN 13 Padang. Practicality test was done by 2 chemistryteachers at SMAN 7 Padang, 1 chemistry teacher at SMAN 13 Padang and 27 XII MIPA5 SMAN 7 Padang students. The instrument was validity and practical questionnaire anddata was analyzed by Cohen Kappa formula. This study produced a buffer module basedon scientific approach with an average kappa moments 0,94 which is very high level ofvalidity. The results of the teacher practicality test and the students practicality testobtained an average of kappa moments in a sequence of 0,91 and 0,73 with a very highlevel and high level of practicalityKeywords : module, buffer, scientific approach, probing and promting 4-D models